Genetic diversity and phylogeny of ITS regions in sweet orange genotypes from San Luis Potosí - Bermúdez-Guzmán, Manuel de Jesús; Tochihuitl-Martiñón, Guillermina Areli; Ramos Cruz, Carlos Miguel; Vargas-Hernández , Juan; Tochihuitl-Martiñón, Anahi (Revista Mexicana de Ciencias Agrícolas, 2026)
The sweet orange is grown in several states of Mexico. Several research centers have citrus germplasm banks, including sweet oranges for genetic improvement. This work aimed to evaluate genetic diversity and perform a phylogenetic analysis based on the internal transcribed spacer (ITS) region of six sweet orange genotypes grown in San Luis Potosí, Mexico. In 2023, leaves of six varieties of sweet orange, known in the region as Sangre de Toro and Valencia, were collected. Genomic DNA was extracted, and ITS regions were amplified by PCR and sequenced. The percentage of identity and genetic distances were determined and a maximum-likelihood phylogenetic tree was generated. The results indicated that the intraspecific variability among C. sinensis genotypes in the ITS region is low to moderate (0-0.07). Particularly, among the population of Citrus sinensis (Sangre de Toro and Valencia varieties) from the regions of Axtla de Terrazas, Chimimexco-Tampacán and El Frijolillo-San Martín in San Luis Potosí, no differences were detected in their ITS regions. It is important to note that the number of samples analyzed was limited; therefore, it is necessary to evaluate a larger set of samples and varieties to obtain more robust conclusions regarding genetic variability in Citrus sinensis in Mexico. The phylogenetic analysis grouped the genotypes of Mexico into group G1, confirming the origin of the varieties with Asian countries (China, Korea and Vietnam), with which the percentage of identity was 100%.